2014
DOI: 10.1016/j.mce.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant gonadotropin-releasing hormone receptor (GnRHR) expression and its regulation of CYP11B2 expression and aldosterone production in adrenal aldosterone-producing adenoma (APA)

Abstract: Aberrant expression of gonadotropin-releasing hormone receptor (GnRHR) has been reported in human adrenal tissues including aldosterone-producing adenoma (APA). However, the details of its expression and functional role in adrenals are still not clear. In this study, quantitative RT-PCR analysis revealed the mean level of GnRHR mRNA was significantly higher in APAs than in human normal adrenal (NA) (P=0.004). GnRHR protein expression was detected in human NA and neoplastic adrenal tissues. In H295R cells trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In a subset of non-pregnant PA patients from our cohort, the aberrant GnRHR was expressed and several of these patients had increased aldosterone secretion40. The GnRHR staining identified in normal and APA adrenal tissues in this study was consistent with previous reports41. Although there was increased expression of GnRHR and LHCGR in wild-type APA patients and less in KCNJ5 mutation adenoma42, we further showed patients harboring CTNNB1 mutations over-expressed GnRHR and LHCGR compared adenomas with KCNJ5 mutation in both genders.…”
Section: Discussionsupporting
confidence: 90%
“…In a subset of non-pregnant PA patients from our cohort, the aberrant GnRHR was expressed and several of these patients had increased aldosterone secretion40. The GnRHR staining identified in normal and APA adrenal tissues in this study was consistent with previous reports41. Although there was increased expression of GnRHR and LHCGR in wild-type APA patients and less in KCNJ5 mutation adenoma42, we further showed patients harboring CTNNB1 mutations over-expressed GnRHR and LHCGR compared adenomas with KCNJ5 mutation in both genders.…”
Section: Discussionsupporting
confidence: 90%
“…We reported the aberrant expression of GnRHR in APA and confirmed by an in vitro model that the chronic activation of GnRHR with GnRH increased CYP11B2 expression and aldosterone production via the calcium signaling pathway (Nakamura et al 2014b). In addition, Kishimoto et al (2016) has recently reported that patients of APA with the higher GnRHR expression showed higher GnRH-stimulated aldosterone response.…”
Section: The Neural Regulators Of Cyp11b2 Expression In Apamentioning
confidence: 57%
“…Recent studies have developed several analytical methods and revealed many novel and key findings regarding the molecular pathogenesis of APA, especially the upregulation system of aldosterone synthase (CYP11B2) expression in APA (Oki et al 2012;Beuschlein et al 2013;Scholl et al 2013;Nakamura et al 2014b;Hattangady et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported somatic CTNNB1 mutations in APA from male patients or non-pregnant females (Scholl et al 2015a, Akerstrom et al 2016, Wu et al 2017. Moreover, although GNRHR and LHCGR overexpression is found in more than 40% of APA (Nakamura et al 2014, Nicolini et al 2014, CTNNB1 mutations are identified only in 5% (Akerstrom et al 2016), with immunohistochemical evidence for β-catenin activation observed in about twothirds of APA . Further studies are necessary to establish the complex mechanisms affected by CTNNB1 mutations in APA.…”
Section: Mutations Affecting β-Catenin Activationmentioning
confidence: 97%